(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This article reveals the results of the study on precocity of cotton lines, such as opening rate of cotton bolls of introgressive lines that were found to ripen 2-13 days earlier than a model sample С-6524 cotton variety. Particularly, in Т-РСМ line the vegetation period made 109 days that was noted to be preucious for 12,3 days than a model sample variety. The selected lines according to their cotton weight in one boll were determined to have high indicators, as well as on germinability of plant seeds. The results of the cluster analysis by economic traits in the lines showed that according to the economic traits, the first cluster included lines T-24 and T-138 were found to be closely related to each other. The line Т-РСМ was included to the third cluster, and it was found that this line was among the varieties with high indicators on all valuable economic traits. As a result of comparative analysis of lines, a new medium-fiber cotton cultivar “Niso” was created with productivity of 38,3-56,5 c/hа, cotton weight in one boll 6,0-6,7 g, precocity of 109,0-112,0 days, fiber, the weight of 1000 seeds 118,0-120,0 g, fiber length of 34,0-35,9 mm, fiber yield of 36,9-41,4 %, relative tensile strength of 34,6 cN/tex.